공공기관에서 진성리더십(Authentic Leadership)이 구성원의 창의적 행동에 미치는 영향: 심리적 임파워먼트의 매개효과와 조직지원인식의 조절된 매개효과 - 김성재(Sung-Jae Kim); 장제욱(Je-Wook Chang); 윤동열(Dong-Yeol Yoon) (대한경영학회지, 2024)
최근 공공기관들이 조직 구성원들의 창의적 행동을 통해 유용한 아이디어를 개발하고 업무 프로세스를 개선하는등 상시적인 혁신에 힘을 기울이고 있다. 이에 본 연구는 상사의 진성 리더십이 조직구성원의 창의적 행동과 심리적임파워먼트에 어떤 영향을 미치는지를 살펴보고, 조직지원인식의 조절된 매개효과에 대해 각종 선행연구를 통해관계를 탐색하고 변수별 영향관계를 살펴보고자 하였다. 이를 위해 A 공공기관 구성원들에게 상사용, 직원용으로 구성한 2가지 설문지를 배포하였고, 최종 236부를통계 분석한 결과는 다음과 같다. 첫째, 상사의 진성리더십은 부하직원의 창의적 행동, 심리적 임파워먼트에 정(+)의영향을 미치는 것으로 확인되었다. 둘째, 심리적 임파워먼트는 창의적 행동에 정(+)의 영향을 미치고, 상사의진성리더십은 심리적 임파워먼트를 매개로 부하직원의 창의적 행동에 정(+)의 영향을 미치는 것으로 나타났다. 셋째, 조직지원인식의 조절 및 조절된 매개효과는 부분적으로 확인되었다. 본 연구를 통해 진정성을 갖춘 리더가조직구성원의 심리적 임파워먼트와 창의적 행동에 긍정적인 영향을 미친다는 것을 실증적으로 규명하였으며, 진성리더십이 조직의 성과에 미치는 영향력을 살펴보았다는 점에서 그 의의가 있다. A공공기관 종사자들만을 대상으로 국한된 표본을 반영하였다는 한계점을 반영하여, 향후 연구에서는 공공기관뿐만 아니라 정부부처, 일반 사기업과 같이 설립 목적이나 성격이 다른 기업들로 연구 대상을 확대하여 비교･분석하는것도 의미가 있을 것으로 판단된다. Recently, the management environment of organizations has undergone a rapid change, and public institutions have introduced policies that pursue management innovation and efficiency at all times. Accordingly, this study sought to examine how the boss's authentic leadership affects the creative behavior and psychological empowerment of organizational members, explore the relationship through various prior studies on the controlled mediating effect of perceived organizational support and examine the influence relationship by variable. In this study, the survey was conducted by workers working in public institutions, The questionnaire was divided into two categories : supervisor and staff, and two different items were composed of. The results of analyzing the survey of 236 questionnaires that answered are as follows. First, it was confirmed that the authentic leadership of the boss had a positive effect on the creative behavior and psychological empowerment of the subordinates. Second, the psychological empowerment had a positive effect on the creative behavior, and the authentic leadership of the boss had a positive effect on the creative behavior of the subordinates through the psychological empowerment as a parameter. Third, The moderating and moderated mediating effects of the perceived organizational support were partially confirmed. This empirical study was meaningful in that authentic leadership of the supervisor has a positive effect on the psychological empowerment and creative behavior of the organizational members, and confirms that the authentic leadership is an important variable that has a positive effect on the organization performance of the public employees. Reflecting the limitation of using a limited sample of workers at public institutions A, In the future research it is also meaningful to expand and compare the research targets to companies with different purpose or personality, such as government departments and private companies, as well as public institutions. KCI Citation Count: 1